Pierre Boulez organised delirium - Potter, Caroline 19XX- (The Boydell Press, 2024)
Exploring the emotional and cultural influences on Pierre Boulez's early works as well as the role surrealism and French culture of the 1930s and 1940s played in shaping his radical new musical concepts
Title from publisher's bibliographic system (viewed on 21 Feb 2024)
Keywords: Boulez, Pierre / 1925-2016 / Criticism and interpretation; Boulez, Pierre -- 1925-2016; Music / 20th century / History and criticism; Surrealismus